2018
DOI: 10.3130/jaabe.17.541
|View full text |Cite
|
Sign up to set email alerts
|

Structural Performance of Recycled Aggregate Concrete Confined by Spiral Reinforcement

Abstract: This paper estimates the structural behavior of recycled aggregate concrete confined by spiral reinforcement. The main test parameters are designed to be the type of aggregates, replacement ratio of recycled aggregates, steel ratio and yield strength of spirals. Specimens subjected to concentrated axial load can be divided into two groups, natural and recycled aggregate specimens, based on the type of coarse aggregate used. The recycled aggregates are designed to be used from 0% to 100% in the specimens. Spira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…While studying the flexural bond behavior of reinforced RAC, Dong et al [13] found a similar mode of reinforcement failure in RAC and NAC and further revealed a decrease in bond strength with an increase in RA content. Kim et al [14] investigated the behavior of RAC confined by spiral reinforcement. The study parameters included replacement level of NA with RA and steel ratio and yield strength of spiral reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…While studying the flexural bond behavior of reinforced RAC, Dong et al [13] found a similar mode of reinforcement failure in RAC and NAC and further revealed a decrease in bond strength with an increase in RA content. Kim et al [14] investigated the behavior of RAC confined by spiral reinforcement. The study parameters included replacement level of NA with RA and steel ratio and yield strength of spiral reinforcement.…”
Section: Introductionmentioning
confidence: 99%